Enoxaparin vs Fondaparinux Dalam Penurunan CK-MB - yedy purwandi sukmawan; Keni Idacahyati; Rezky Fahrizal Firdaus (Fakultas Farmasi Universitas Setia Budi, 2020)
Ischemic Heart Disease (Non ST Elevated Myocardial Infarction-NSTEMI) is the leading cause of death in Indonesia after Stroke. Enoxaparin and Fondaparinux are the drugs of choice for this condition. However, there is a little study about these drugs in Indonesian people. Therefore, the objective of the study is to determine the effectivity of enoxaparin and fondaparinux in CK-MB reduction in Indonesian people. The methods of the study is retrospective observational study. A total of 43 patients were met inclusion criteria (32 in the enoxaparin group and 11 in the fondaparinux group). The outcome of the study was CK-MB reduction and the time of dyspnea was disappeared. The results of the study showed no statistic difference between enoxaparin and fondaparinux in reducing CK-MB blood plasma level (-29.00 vs -33.09; p 0.715), and also the time of dyspnea was disappeared (3.44 vs 3.09 days; p 0.347). Therefore, the choice of these agents are based on clinical condition, adverse effects and pharmacoeconomic aspects.